Zenon Fisz in Search for the Shape of the World: Opowiadania i krajobrazy. Szkice z wędrówek po Ukrainie - Лавскі, Ярослав (Київського національного університету імені Тараса Шевченка, 2025)
The essay brings back the forgotten work of the outstanding Polish romantic writer, Zenon Leonard Fisz (1820–1870), entitled: Opowiadania i krajobrazy. Szkice z wędrówek po Ukrainie. [Stories and Landscapes. Sketches from the Wanderings in Ukraine] (vol. 1-2, Vilnius 1856). The work is an attempt to find a new genre form that would accommodate the paradoxical tendencies of the world in an age of great civilisational and cultural transformation. It combines the elements of travel writing, storytelling, sketching and journalism with elements of historical narrative (two long short stories are included in the travel narrative). Ultimately, as the author claims, Fisz found a form to express the chaos of the transformations of modernity, yet he failed to find the answer to the question about the consequences that these changes would bring for his beloved Ukraine, where he lived. The work and its form got out of control, as the subsequent parts, which were announced at the end of volume 2, were never written. Fisz’s work may be described as proto-reportage, emerging from the tradition of travel writing at the moment when the itinerarium form was already exhausted and a new genre was taking shape. His narrative intertwines the planned route of travel with encounters of unforeseen phenomena, while digressions, quotations, polemics, and inserted stories enrich the structure. Personal experience blends with literary preparation; solemnity shifts into gentle irony or melancholy; polemical energy gives way to realist observation or contemplative elevation. In conclusion, Zenon Fisz succeeded in finding a literary form to capture the transformations of a civilisation in flux, yet he failed to answer the ultimate question of where the “Great Transformation” was leading. This tension – between melancholy and change, lyricism and epic, “Source” and “Mouth” of the river – points to the existential limits of his search. To find the form but not the answer was, perhaps, to cross the boundary where madness begins. His descent into illness, which prematurely ended both his literary and civic activity, may be read as the tragic consequence of this inner conflict.

Есе повертає із забуття творчість видатного польського романтичного письменника Зенона Леонарда Фіша (1820–1870), а саме його працю Opowiadania i krajobrazy. Szkice z wędrówek po Ukrainie [Оповідання і краєвиди. Нариси з мандрів по Україні] (т. 1–2, Вільно, 1856). Твір є спробою віднайти нову жанрову форму, здатну вмістити парадоксальні тенденції доби великих цивілізаційних та культурних трансформацій. Він поєднує елементи подорожніх нотаток, оповіді, нарису та публіцистики з елементами історичної нарації (у подорожній оповідь інтегровано дві розлогі новели). Зрештою, як стверджує автор, Фіш знайшов форму для вираження хаосу модерних перетворень, проте так і не зумів дати відповідь на запитання про наслідки цих змін для його улюбленої України, в якій він мешкав. Твір і його форма вийшли з-під контролю, адже наступні частини, анонсовані наприкінці другого тому, так і не були написані.
Зенон Фіш у пошуках форми світу: Оповідання і краєвиди. Нариси з мандрів по Україні
Keywords: Zenon Leonard Fisz; Ukraine; form; civilisational transformations; travel; Зенон Леонард Фіш; подорож; Україна; форма; цивілізаційні трансформації